A 3D-printed handheld device for quick citrus tissue lysis and nucleic acid extraction - Chia-Wei Liu; Brent Kalish; Sohrab Bodaghi; Georgios Vidalakis; Hideaki Tsutsui (Advances in Sample Preparation)
Abstracts: A 3D-printed handheld device has been developed for rapid and efficient sample preparation, extracting pathogen total nucleic acids from citrus leaves for downstream molecular analysis. With its high-speed motor, knurled lysis chamber for rapid sample lysis, and quick nucleic acid extraction using cellulose paper disks (Whatman CHR1), this device can yield ready-to-use DNA and RNA in just 12 min. All components, except for the motor, wiring, and paper disks, were printed in-house using a PolyJet 3D printer with photosensitive resins. The device was optimized for maximum sample lysis by evaluating operation voltages and chamber features, as measured by DNA and RNA concentrations using a Qubit fluorometer and quantification cycle (Cq) values obtained through qPCR assays. The results showed that the lysis chamber with internal knurling and the motor operated at 7.5 V was sufficient for effective sample lysis in 1 min, achieving RNA concentrations up to 87.6 % of those obtained with mortar-and-pestle grinding. Paper disk washing and elution conditions were also optimized using a NanoDrop spectrophotometer and qPCR assays, where two 1-minute washes and a 100 µL elution volume resulted in the highest purity and lowest Cq value. The optimized handheld device was validated with citrus sources infected with Citrus tristeza virus (CTV) and Spiroplasma citri (S. citri), demonstrating high detection accuracy (100 %) and low assay variation (CV < 3.8 %) in qPCR-based analysis. Based on these successful results, this device is expected to be broadly applicable to similar viral and bacterial pathogens affecting plants.